Hubungan Usia, Masa Kerja, dan Kebiasaan Merokok dengan Kejadian Musculoskeletal Disorders - Maharani Nusara Ardhi; Renni Renni (Pusat Riset dan Inovasi Nasional, 2026)
Musculoskeletal Disorders (MSDs) are disorders of the skeletal muscles that can range from very mild to very painful. Repeated static loads over a long period of time can cause damage to joints, ligaments, and tendons. Musculoskeletal disorders can occur due to several factors, including occupational factors, individual factors, psychosocial factors, and environmental factors. This study aims to analyze the relationship between age, length of service, and smoking habits with musculoskeletal disorders in furniture craftsmen. This study used an observational analytical study with a cross-sectional design. The sample used a total population of 51 workers. Data collection techniques were observation and filling out the Nordic Body Map (NBM) questionnaire. Data analysis used the Somers'd. The results of the analysis showed that there was a relationship between age (p value = 0.015), length of service (p value = 0.001), and smoking habits (p value = 0.000) with the incidence of Musculoskeletal Disorders (MSDs).